The chronological study Bible : New King James version. (Nashville, Tenn. : Thomas Nelson, 2008)
The Chronological Study Bible is the only study Bible that presents the text of the New King James Version in chronological order -- the order in which the events actually happened. Immerse yourself in the beautifully designed pages, full-color illustrations, easy-to-read charts and detailed maps and timelines. Dig deeper into ancient civilizations, religions and governments and the cultures and peoples that continue to shape our world today. Explore further the hidden connections in Scripture through one dramatic historical timeline. - Publisher.
Before the patriarchs (creation-2000 B.C.) -- Patriarchs, Israel's ancestors, (2000-1500 B.C.) -- Rise of a unified people (1500-1200 B.C.) -- From tribes to a nation (1200-930 B.C.) -- Fall of two nations (930-586 B.C.) -- Exile and return (586-332 B.C.) -- Between the two Testaments (332-37 B.C.) -- Coming of the Messiah (37 B.C.- A.D. 30) -- Church age (A.D. 30-100) -- Cultural and historical topics -- Glossary -- Concordance -- Index of Scripture passages.
Includes index.
nbl-10 rel
Keywords: Bible -- Chronology; Bible -- Study and teaching